Social Equality and the Corporate Governance of a Property-Owning Democracy - Wilesmith,John (2015)
In recent years, a number of theorists have argued that Rawls's vision of a property-owning democracy seems like a promising way to institutionalise an ideal of social equality. In this paper, I distinguish two economic aims that appear central to these accounts of social equality: widespread security and control. I then argue that, insofar as Rawls's property-owning democracy retains many large-scale corporations, it is poorly placed to realise these two economic aims unless it is supplemented with an adequate regime of corporate governance. I go on to assess three possible regimes of corporate governance for a property-owning democracy: (1) investment fund activism; (2) worker-managed firms; and (3) labour-capital partnerships. I argue that all three regimes offer different trade-offs between widespread economic security and control; however, there are social egalitarian reasons - albeit of a provisional nature - to see regime (3) as a superior option to regimes (1) and (2).